Pengaruh Budaya Organisasi dan Lingkungan Kerja Fisik Terhadap Kinerja Pegawai Pada Dinas Pendidikan Provinsi DKI Jakarta - Nursaputri, Heni; Zulkarnain, Iskandar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study was to determine the influence of Organizational Culture and Physical Work Environment on Employee Performance at the DKI Jakarta Provincial Education Office, both partially and simultaneously. The method used was quantitative. The population in this study was 200 respondents, with a sample size of 67 respondents, determined using the Slovin formula and convenience sampling techniques. Based on the results of the study, it shows that organizational culture (X1) and physical work environment (X2) have a significant effect on employee performance with the regression equation Y = 11.791 + 0.424 (X1) + 0.222 (X2). The organizational culture hypothesis test obtained a calculated t value > t table or (6.246 > 1.997) with sig. (0.000 < 0.05). Thus, Ho1 was rejected and Ha1 was accepted, meaning there was a significant influence of organizational culture on employee performance. The results of the physical work environment hypothesis obtained a calculated t value > t table or (4.995 > 1.997) with sig. (0.000 < 0.05). Thus, Ho2 is rejected and Ha2 is accepted, meaning there is a significant influence of the physical work environment on employee performance. The hypothesis test obtained a calculated F value > F table or (22.911 > 3.14). Thus, Ho3 is rejected and Ha3 is accepted. This means there is a simultaneous significant influence of organizational culture and the physical work environment on employee performance, this can also be strengthened by the Sig. value < 0.05 or (0.000 < 0.05).